1974
DOI: 10.1128/iai.9.2.419-429.1974
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Adherence of Streptococcus mutans to Smooth Surfaces II. Nature of the Binding Site and the Adsorption of Dextran-Levan Synthetase Enzymes on the Cell-Wall Surface of the Streptococcus

Abstract: The mechanism of adsorption of the Streptococcus mutans enzymes responsible for the synthesis of insoluble dextran-levan to the S. mutans cell-wall binding sites has been studied. Certain characteristics of these binding sites are presented. The adsorption of these enzymes to the cell surface occurred rapidly without the addition of a source of energy and over a pH range of 3 to 11. The adsorption was inhibited by soluble dextran, probably due to the strong affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
85
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 22 publications
8
85
1
Order By: Relevance
“…It is of interest that antibody directed against extracellular GTase significantly inhibited the cell-associated GTase activity which resulted in the marked reduction in adherence to a glass surface of viable S. mutans cells ( Table 2). It has been found that a portion of the extracellular GTase of S. mutans will bind to the surface of S. mutans cells (18,20,25,28,29), and therefore significant inhibition of GTase activity and cell adherence can be expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest that antibody directed against extracellular GTase significantly inhibited the cell-associated GTase activity which resulted in the marked reduction in adherence to a glass surface of viable S. mutans cells ( Table 2). It has been found that a portion of the extracellular GTase of S. mutans will bind to the surface of S. mutans cells (18,20,25,28,29), and therefore significant inhibition of GTase activity and cell adherence can be expected.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown by in vivo (39) and in vitro (13,16,(28)(29)(30)33) studies that the ability of Streptococcus mutans cells to adhere to smooth surfaces is mediated by glucan synthesis from sucrose by glucosyltransferase (GTase). The GTase of S. mutans is produced extracellularly and is also present in a cell-associated form.…”
mentioning
confidence: 99%
“…Early colonisation with mutans streptococci is associated with the prevalence of ECC in preschool children (5). Multiple virulence factors of Streptococcus mutans, including its ability to produce and survive in acidic environments (6) and to express a water-insoluble membrane-bound polysaccharide providing bacterial attachment (7), support the theory that it is the primary microbial cause of dental caries (8). Other factors affecting the level of S. mutans, including salivary pH and flow, and diet, also increase the risk of caries (9).…”
mentioning
confidence: 99%
“…On the other hand, it was found that serotype e MT703 cell walls were not susceptible to the L-11 enzyme, whereas B2 cell walls of the same serotype e were significantly lyzed by the enzyme. This indicates that the presence of other cell-surface components such as fuzzy coat (4, 37), glucan-binding proteins (24,32,46), and exogenous cell-bound glucans (15,25,31,35,44,46) may also affect the susceptibility of S. mutans cell walls to the lytic enzyme. However, conclusion about the cause(s) of the insensitivity of MT703 (e) , AHT (g) , and 6715 (g) cell walls to the enzyme should await further examination.…”
Section: Discussionmentioning
confidence: 99%